Cover Feature: Enhancement of Mass and Charge Transfer during Carbon Dioxide Photoreduction by Enhanced Surface Hydrophobicity without a Barrier Layer (Chem. Eur. J. 43/2022). Issue 43 (11th July 2022) - Liu, Xuan; Huang, Chengxi; Ouyang, Bo; Du, Yongping; Fu, Boyu; Du, Zhengwei; Ju, Qiang; Ma, Jingjing; Li, Ang; Kan, Erjun
Abstract : What you want, where you want it : Fewer H2 O and more CO2 molecules can be delivered directly to an in‐situ hydrophobic surface for the photocatalytic reduction of CO2 to CH3 OH. A traditional hydrophobic surface would hinder charge transfer, while for a hydrophilic surface, the low solubility and slow diffusion rate limit the mass transfer of CO2 . Our in‐situ surface fluorination strategy overcomes such mass and charge‐transfer limitations enhancing the performance of CRR, which is a promising route for the clean utilization of renewable resources. More information can be found in the Research Article by A. Li, E. Kan, and co‐workers (DOI: 10.1002/chem.202201034 ).